Influence of Workplace Environment, Occupational Health and Safety, and Organizational Dedication on Nurse Performance - Rista Vindu (Safety and Health for Medical Workers, 2024)
Objective: This study aims to investigate the relationship between the work environment, occupational health and safety (OHS), organizational commitment, and nurse performance in a hospital setting.Method: A quantitative approach was employed, gathering data from 83 nurse respondents at Madiun Hospital. Data analysis was conducted using the structural equation modeling (SEM) approach with the partial least squares technique through Smart PLS.Findings: The findings reveal significant positive correlations between the work environment and organizational commitment, OHS and organizational commitment, OHS and nurse performance, as well as organizational commitment and nurse performance. However, no significant relationship was found between the work environment and nurse performance.Novelty: This study contributes by highlighting the importance of a conducive work environment and OHS efforts in enhancing organizational commitment and nurse performance in hospitals.Research Implications: The implications of this study underscore the need to focus on improving the work environment and OHS in hospitals to enhance organizational commitment and nurse performance. This can aid hospital management in developing strategies to improve service quality and patient satisfaction.